Rotor-wing interaction phenomena for the ERICA tilt-wing rotorcraft configuration in the DNW-LLF wind tunnel - Bruin, A. de; Schneider, O. (My University, 2015)
As part of the EU co-funded NICETRIP project a 1:5 scale model was tested in the 9.5x9.5 m2 test section of the low speed DNW-LLF wind tunnel in June-July 2013 (see Ref. 1). The model design and manufacturing was largely done by NLR, with inputs from TsAGI (fuselage shells), ONERA (rotor balances and blade design) and Eurocopter (rotor hub design). Model pre-testing, including ground vibration tests and model control in the wind tunnel, was done by DLR. The overall project was led by Agusta Westland. The test matrix consisted of 7 trimmed conditions in helicopter; conversion & aircraft mode. For each trimmed condition a comprehensive number of variations (incidence, sideslip, nacelles, tilting outboard wing angles, flaps, flaperons, rudder and elevator angles, collective and cyclic blade pitch angle settings) were performed in order to provide data for the flight dynamic model data-base. In total, over 400 different flight conditions, including an exploration towards the boundary of the conversion corridor, were measured. The model has a wing span of 3 m and two 1.48 m diameter rotors and is heavily instrumented. Model trimming was enabled by a model-pilot inter-face from DLR to operate 16 (!) remote controls (Ref. 2). Total forces, rotor and tail forces were measured with 6-component balances. Flaperon, flap, rudder and elevator moments were measured with one-component local balances. In addition various local loads and temperatures were measured and monitored for safety reasons. For each flight condition, over 800 parameters were recorded; consisting of about 50 parameters from balance loads, strain gauges and accelerometer measurements, flight control positions, power required and 678 static and 55 dynamic model pressures. The tests resulted in an extensive and valuable database for the validation of the ERICA tilt-wing/tilt-rotor concept. The relatively large rotors, placed at the wing tips and operating close to the wing leading edge, create significant wing-rotor interference effects, especially during high thrust conditions. Each blade passage over the wing leading edge not only leads to a periodic loading effect on the blade, but the blade wake and blade tip vortex passage over the wing also creates periodic loading of the wing. In turn these unsteady loadings can be a driving factor for rotor and wing vibrations. In a previous paper the unsteady rotor loads and nacelle vibration levels observed during the DNW-LLF tests have been investigated (Ref. 3). In the present paper the focus will be on the steady but particularly on the unsteady pressures measured on the outer wing and their correlation with blade passage, observed vibration levels and flaperon loadings.
Keywords: Test & Evaluation